Pendidikan Kebahagiaan dalam Revolusi Industri 4 - Wahyudi Setiawan; Fitriah M Suud; Moh Toriqul Chaer; Azam Syukur Rahmatullah (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2018)
Abstract: Happiness is the essence of everyone's life. Its existence in itself has always been the driving force of man to do the best in his life. Civilization is constantly changing, but the happiness and meaningfulness of life remain the ultimate human choice of life. The industrial revolution 4 challenges people to do more quickly to achieve the quality of life through technology. The happiness education and meaningfulness of life are challenged to face the massive disruptions happening globally. In the end, the millennial generation as the holder of the industrial revolution 4 will be a superior generation of intelligent and qualified in running a global civilization. Live with a high level of intelligence that is comparable to quality life. This paper will present a discussion to open the higher-order thinking with a combination of the dimensions of religiosity and science as well as a healthy personality.